2021
DOI: 10.1093/brain/awab154
|View full text |Cite
|
Sign up to set email alerts
|

A passive and objective measure of recognition memory in Alzheimer’s disease using Fastball memory assessment

Abstract: Earlier diagnosis of Alzheimer’s disease requires biomarkers sensitive to associated structural and functional changes. While considerable progress has been made in the development of structural biomarkers, functional biomarkers of early cognitive change, unconfounded by effort, practice and level of education, are still needed. We present Fastball, a new EEG method for the passive and objective measurement of recognition memory, that requires no behavioural memory response or comprehension of the task . Young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Moreover, while we ensured that (un)familiar faces were (un)familiar for every participant, the familiarity contrast could have even been stronger overall and strengthened by independent behavioral measures (see methods and discussion above). This high sensitivity coupled with the high specificity (i.e., no hint of a neural FIFE in the case of prosopdysgnosia JG, in line with behavioral data) and the focal localization of the effect in all individuals (i.e., allowing to use a small number of recording channels) makes this paradigm highly desirable for implicit evaluation of human face identity knowledge in individual participants, with practical implications in clinical (i.e., as biomarkers of neurodevelopmental or neurodegenerative disorders in face identity recognition, e.g., Autism Spectrum Disorder or Alzheimer’s disease 83 , 84 ) and forensic research for instance 85 . In this vein, providing that the stimulus set remains large and is adequately adjusted to new populations, future studies could build on the present paradigm to evaluate (1) the relationship between the magnitude of the neural FIFE and the degree of familiarity with the faces (i.e., beyond a simple contrast between familiar and unfamiliar faces) and (2) its sensitivity to personally familiar and/or familiarized (learned) face identities on an individual basis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while we ensured that (un)familiar faces were (un)familiar for every participant, the familiarity contrast could have even been stronger overall and strengthened by independent behavioral measures (see methods and discussion above). This high sensitivity coupled with the high specificity (i.e., no hint of a neural FIFE in the case of prosopdysgnosia JG, in line with behavioral data) and the focal localization of the effect in all individuals (i.e., allowing to use a small number of recording channels) makes this paradigm highly desirable for implicit evaluation of human face identity knowledge in individual participants, with practical implications in clinical (i.e., as biomarkers of neurodevelopmental or neurodegenerative disorders in face identity recognition, e.g., Autism Spectrum Disorder or Alzheimer’s disease 83 , 84 ) and forensic research for instance 85 . In this vein, providing that the stimulus set remains large and is adequately adjusted to new populations, future studies could build on the present paradigm to evaluate (1) the relationship between the magnitude of the neural FIFE and the degree of familiarity with the faces (i.e., beyond a simple contrast between familiar and unfamiliar faces) and (2) its sensitivity to personally familiar and/or familiarized (learned) face identities on an individual basis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Traikapi and Konstantinou (2021) found disruptions in the gamma waves in AD patients and discovered that gamma stimulation could potentially reduce the severity of AD symptoms and slow cognitive decline [129]. Additionally, a study by Stothart et al (2021) showed that EEG detected a significant difference in the recognition memory between AD patients and healthy older adults when they were tested using a fastball memory assessment [140].…”
Section: Eeg As a Biomarker In Admentioning
confidence: 99%
“…EEG can detect electrical activity in the brain, record brainwave patterns, and reflect the underlying brain function. In 2021, Stothart et al [118] presented a new EEG method, Fastball, to measure recognition memory passively and objectively, which is fast and convenient and requires no comprehension of the task or behavioral response. It demonstrated that Fastball could distinguish AD from healthy individuals with high accuracy, providing a passive, objective, non-invasive, quick-toadminister method for the assessment of cognition in dementia.…”
Section: Imaging Techniquesmentioning
confidence: 99%